Quality of life of stoma patients: temporary ileostomy versus colostomy - Silva, M.A.; Rathnayake, G.; Deen, K.I. (Springer-Verlag, 2003)
Ileostomy for proximal diversion as a preferred option over colostomy has been a recent topic of interest. Our study evaluated the quality of life (QOL) of patients with a temporary ileostomy and compared it with that of patients with a temporary colostomy. The QOL of 25 patients with an ileostomy(median age 42 years, range 22-76 years) was compared with that for 25 patients with a colostomy (median age 44 years, range 18-70 years). Indications for a stoma were rectal carcinoma, trauma, inflammatory bowel disease, anastomotic leak, or incontinence following an operative procedure for rectal prolapse. The study was conducted at a median of 8 weeks (range 6-16 weeks) for ileostomy patients and of 9 weeks (range 5-17 weeks) for colostomy patients following stoma creation. A self-administered structured questionnaire was used, with responses obtained for 10 QOL questions on a visual analog rating scale (0-100 mm); they were graded good (71-100), satisfactory (31-70), or poor (0-30). Altogether, 22 (88%)patients with an ileostomy, compared with 16 (64%) patients with a colostomy, were able to purchase their stomal appliances ( p = 0.09, chi(2): NS). Effluent was tolerable in 18 (72%) patients with an ileostomy compared with 7 (28%) patients with a colostomy ( p = 0.002, chi(2)). Appetite was not affected in any of the patients with an ileostomy (100%), compared with 64% of patients with a colostomy ( p = 0.002, chi(2)), travel by public transport 32% compared to 28% with colostomy (NS), dress in 20% compared to 24% with colostomy (NS), and daily activities 28% compared to 24% with colostomy (NS). Moreover, 68% with an ileostomy did not have a problem with hygiene compared with 40% with a colostomy (NS); 95% with an ileostomy abstained from sexual activity compared with 81% with a colostomy ( p = 0.21, chi(2): NS). Both ileostomy and colostomy resulted in significant QOL impairment. However, with ileostomy, the effluent was more tolerable, had less of an impact on personal hygiene, and preserved the appetite compared with colostomy. There were no differences in travel, dress, daily chores, or sexual activity between the two groups.
Indexed in MEDLINE
Keywords: Colostomy; Ileostomy; Quality of Life; Surgical Stomas-physiology